Color-discrimination threshold determination using pseudoisochromatic test plates - Jurasevska, Kaiva; Ozolinsh, Maris; Fomins, Sergejs; Gutmane, Ausma; Zutere, Brigita; Pausus, Anete; Karitans, Varis (Frontiers in Psychology, 2014)
We produced a set of pseudoisochromatic plates for determining individual color-difference thresholds to assess test performance and test properties, and analyzed the results. We report a high test validity and classification ability for the deficiency type and severity level [comparable to that of the fourth edition of the Hardy–Rand–Rittler (HRR) test]. We discuss changes of the acceptable chromatic shifts from the protan and deutan confusion lines along the CIE xy diagram, and the high correlation of individual color-difference thresholds and the red–green discrimination index. Color vision was tested using an Oculus HMC anomaloscope, a Farnsworth D15, and an HRR test on 273 schoolchildren, and 57 other subjects with previously diagnosed red–green color-vision deficiency.